Adherence to dietary guidelines and mortality: a report from prospective cohort studies of 134, 000 Chinese adults in urban Shanghai. Issue 2 (18th June 2014) - Yu, Danxia; Zhang, Xianglan; Xiang, Yong-Bing; Yang, Gong; Li, Honglan; Gao, Yu-Tang; Zheng, Wei; Shu, Xiao-Ou
ABSTRACT: Background: A higher adherence to dietary recommendations, such as the Dietary Approaches to Stop Hypertension (DASH) and the Alternative Healthy Eating Index (AHEI), has been associated with lower morbidity and mortality from chronic diseases in Western populations. However, the health benefits of following the Dietary Guidelines for Chinese remain unknown. Objective: We examined adherence to the Chinese Food Pagoda (CHFP) in association with total and cause-specific mortality and compared associations with those of the DASH and AHEI. Design: Participants included 61, 239 men and 73, 216 women (aged 40–74 y) from 2 population-based prospective studies in Shanghai, China. Habitual dietary intakes were assessed at baseline in-person interviews by using validated food-frequency questionnaires. Deaths and underlying causes were identified through the Shanghai Vital Statistics Registry and follow-up home visits. Results: We documented 2954 deaths in men and 4348 deaths in women during mean follow-ups of 6.5 and 12.0 y, respectively. A higher CHFP score was associated with lower total mortality with multivariable-adjusted HRs of 0.67 (95% CI: 0.60, 0.75) in men and 0.87 (95% CI: 0.80, 0.95) in women when extreme quartiles were compared (both P -trend < 0.005). Decreased risks associated with a higher CHFP score were observed for cardiovascular disease, cancer, and diabetes mortality, particularly in men. A significantly lower total mortality was shown for adherence to specific recommendations on vegetables, fruit, legumes, fish, and eggs but not grains, dairy, meat, fat, and salt. A higher DASH score and AHEI also predicted lower mortality from all causes, cardiovascular disease, and diabetes but not cancer. Conclusions: A greater compliance with Chinese or US dietary guidelines is associated with lower total mortality in Chinese adults. Favorable associations are more evident in men than women and more consistent for cardiometabolic mortality than cancer mortality.